Non-pharmacological methods of treating chronic non-specific neck pain, possibilities of radiofrequency denervation: A review - Maksim I. Gaydash; Haider N.A. Akif; Mikhail G. Zonov (ZAO "Consilium Medicum", 2023)
Chronic non-specific neck pain (CNSNP), or cervicodynia, is a common pathology that significantly reduces the quality of life of patients. It is believed to be based on degenerative and dystrophic changes in the spine, as well as myofascial pain syndrome. Currently, a comprehensive approach is used in the treatment of CNSNP, including kinesitherapy, ergotherapy, manual therapy, and cognitive-behavioral therapy. In case of ineffectiveness of conservative patient management methods, radiofrequency denervation is used, which is an effective and safe procedure for reducing the severity of pain syndrome. The results of the use of radiofrequency denervation in CNSNP are discussed.